Screening and grounding system for residential, commercial and industrial buildings (Ciencias de la Ingeniería y Aplicadas, 2023)
Lightning Shielding Systems together with grounding systems provide protection for people, animals and objects. This document establishes the procedure for the development of these systems, for this the following sequence is determined: it starts modeling the building using SOLIDWORKS software, then uses the IEC-standard62305-2 to perform a risk analysis based on the shape of the building, then for the design of the screening system the electrogeometric method is applied. In the case of the grounding system, the soil resistivity measurement is performed, and through the IP2Win open source program, the terrain model is obtained, thus, the grounding system is calculated using the procedure established in the IEEE std-80. In this case the methodology was applied to the building of the House of Ecuadorian Culture "Benjamín Carrión Núcleo de Cotopaxi", which does not have protection systems against atmospheric discharges and contains objects of historical interest to protect. The results obtained allow the determination of the appropriate location of the lightning rods, as well as the paths of the wiring and the structure of the grounding system with which an adequate protection against atmospheric discharges is achieved.
Keywords: Electrical risk; Soil resistivity; Atmospheric discharges